VSO: Visual Semantic Odometry - Lianos, Konstantinos-Nektarios; Schönberger, Johannes L.; Pollefeys, Marc; Sattler, Torsten (2018 European Conference on Computer Vision, 2018)
Robust data association is a core problem of visual odometry, where image-to-image correspondences provide constraints for camera pose and map estimation. Current state-of-the-art direct and indirect methods use short-term tracking to obtain continuous frame-to-frame constraints, while long-term constraints are established using loop closures. In this paper, we propose a novel visual semantic odometry (VSO) framework to enable medium-term continuous tracking of points using semantics. Our proposed framework can be easily integrated into existing direct and indirect visual odometry pipelines. Experiments on challenging real-world datasets demonstrate a significant improvement over state-of-the-art baselines in the context of autonomous driving simply by integrating our semantic constraints.